2014
DOI: 10.3389/fnbeh.2014.00338
|View full text |Cite
|
Sign up to set email alerts
|

Resting state functional connectivity predicts neurofeedback response

Abstract: Tailoring treatments to the specific needs and biology of individual patients—personalized medicine—requires delineation of reliable predictors of response. Unfortunately, these have been slow to emerge, especially in neuropsychiatric disorders. We have recently described a real-time functional magnetic resonance imaging (rt-fMRI) neurofeedback protocol that can reduce contamination-related anxiety, a prominent symptom of many cases of obsessive-compulsive disorder (OCD). Individual response to this interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 51 publications
(63 reference statements)
0
37
0
1
Order By: Relevance
“…To date, several studies show that neurofeedback training causes behavioral effects that are specific to the functional role of the targeted cortical area (Weiskopf et al, 2004; Bray et al, 2007; Caria et al, 2007; Rota et al, 2009; Shibata et al, 2011; Scharnowski et al, 2012, 2015; Robineau et al, 2014; Koush et al, 2015; Scharnowski and Weiskopf, 2015). Even more importantly, real-time fMRI neurofeedback training has also been shown to have therapeutic effects in chronic pain patients (deCharms et al, 2005; Guan et al, 2015), Parkinson’s disease (Subramanian et al, 2011), tinnitus (Haller et al, 2010), depression (Linden et al, 2012; Young et al, 2014), obsessive-compulsive disorder (Scheinost et al, 2013, 2014), spider phobia (Zilverstand et al, 2015), and addiction (Li et al, 2013; Karch et al, 2015; Kirsch et al, 2015; Hartwell et al, 2016). Especially for clinical applications of neurofeedback it is crucial that the learning effects persist beyond the initial training period and that voluntary control transfers to situations without neurofeedback information.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies show that neurofeedback training causes behavioral effects that are specific to the functional role of the targeted cortical area (Weiskopf et al, 2004; Bray et al, 2007; Caria et al, 2007; Rota et al, 2009; Shibata et al, 2011; Scharnowski et al, 2012, 2015; Robineau et al, 2014; Koush et al, 2015; Scharnowski and Weiskopf, 2015). Even more importantly, real-time fMRI neurofeedback training has also been shown to have therapeutic effects in chronic pain patients (deCharms et al, 2005; Guan et al, 2015), Parkinson’s disease (Subramanian et al, 2011), tinnitus (Haller et al, 2010), depression (Linden et al, 2012; Young et al, 2014), obsessive-compulsive disorder (Scheinost et al, 2013, 2014), spider phobia (Zilverstand et al, 2015), and addiction (Li et al, 2013; Karch et al, 2015; Kirsch et al, 2015; Hartwell et al, 2016). Especially for clinical applications of neurofeedback it is crucial that the learning effects persist beyond the initial training period and that voluntary control transfers to situations without neurofeedback information.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study found that DMN upregulation learning and down-regulation learning scores are partly determined by preneurofeedback resting-state eigenvector centrality of the PCC/PCu (Skouras & Scharnowski, 2019). Further, another study observed resting state connectivity to be predictive for neurofeedback learning success in patients with obsessive-compulsive disorder (Scheinost et al, 2014). These findings should be replicated and tested to assess whether they are generalizable.…”
Section: Activity-vs Connectivity-based Neurofeedbackmentioning
confidence: 97%
“…The outcome of an intervention is influenced by multiple factors [70], including pretreatment individual differences. The identification of markers that predict treatment response [83] and the use of repeated training sessions may increase the number of participants that respond to rt-fMRI NFTs.…”
Section: Discussionmentioning
confidence: 99%